2019
DOI: 10.1007/s12350-017-0922-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 99mTc-Hydroxymethylene diphosphonate scintigraphy for diagnosis of transthyretin cardiac amyloidosis

Abstract: Tc-HMDP scintigraphy is as accurate as Tc-DPD or Tc-PYP, and may therefore de facto be considered a valuable tool for the diagnosis of TTR CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…20 Similar findings have been reported with 18 F-florbetabir from other laboratories 22 and with another amyloid specific PET tracer, 18 F-florbetaben. 23 The current study by Capelli et al 21 confirms earlier findings of smaller studies and case reports 13,14 as well as the large-scale study by Gillmore et al 17 showing the potential of 99m Tc-HMDP nuclear imaging in patients with suspected TTR-CA, to reliably differentiate those from AL-CA and other causes of LVH. The biggest limitations, as the authors point out, are small sample size and lack of biopsy confirmation in several patients.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…20 Similar findings have been reported with 18 F-florbetabir from other laboratories 22 and with another amyloid specific PET tracer, 18 F-florbetaben. 23 The current study by Capelli et al 21 confirms earlier findings of smaller studies and case reports 13,14 as well as the large-scale study by Gillmore et al 17 showing the potential of 99m Tc-HMDP nuclear imaging in patients with suspected TTR-CA, to reliably differentiate those from AL-CA and other causes of LVH. The biggest limitations, as the authors point out, are small sample size and lack of biopsy confirmation in several patients.…”
supporting
confidence: 87%
“…The biggest limitations, as the authors point out, are small sample size and lack of biopsy confirmation in several patients. 21 Their results are overall positive; however, there are a number of unanswered. Other than local availability, are there specific benefits of using 99m Tc-DPD over 99m Tc-PYP and 99m Tc-HMDP and vice versa, such as ease of labeling (radiochemistry), differences in cost, image quality, radiation exposure etc.?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 2947 studies, we identified 27 meeting the inclusion criteria, including data on 3493 patients ( Figure ). Twenty‐two studies evaluated the performance of CMR in diagnosing either cardiac amyloidosis or ATTR amyloidosis, with a further five studies assessing the diagnostic performance of nuclear scintigraphy . Seventeen studies assessing the performance of index tests in the diagnosis of cardiac amyloidosis included patients with a range of cardiac conditions, whereas 9 out of 11 studies diagnosing ATTR amyloidosis included patients with ATTR or AL amyloidosis only.…”
Section: Resultsmentioning
confidence: 99%
“…Недавно разработанный консенсусом специалистов алгоритм для неинвазивной диагностики АС отводит центральную роль сцинтиграфии с 99mTc-PYP/DPD/HMDP [3]. Данные радиотрейсеры позволяют диагностировать транстиретиновый амилоидоз (ATTR) сердца с достаточно высокой чувствительностью [6], но не полностью специфичны [7][8][9][10][11]. Многоцентровое исследование 1217 пациентов показало положительную прогностическую ценность для ATTR АС в 100% (доверительный интервал 98,0-100) у пациентов с подозрением на амилоидоз по данным эхокардиограммы или МРТ и отсутствием моноклонального белка в сыворотке крови или моче [7].…”
Section: список литературы/Referencesunclassified